A 7-nt nucleotide sequence variant within the sheep KDM3B gene affects female reproduction traits. Issue 7 (12th December 2022) - Kang, Yuxin; Bi, Yi; Tang, Qi; Xu, Hongwei; Lan, Xianyong; Zhang, Qingfeng; Pan, Chuanying
Abstract: Lysine demethylase 3B ( KDM3B ) gene is a histone demethylase, demonstrating specific demethylation of the histone H3 lysine 9. It was detected as a sheep reproductive candidate gene by genome-wide scans, and related studies also showed its significance in female reproductive process. However, rare study researched its polymorphism. Herein, we hypothesized that the polymorphisms of KDM3B gene were associated with sheep reproduction traits. A 7-nt nucleotide sequence variant (rs1088697156) within KDM3B gene was identified in a total of 888 individuals, including the Australian White (AUW) sheep and Lanzhou Fat-tailed (LFT) sheep. II (insertion/insertion) and ID (insertion/deletion) genotypes of 7-nt variant were detected, which were at Hardy-Weinberg equilibrium (HWE) in detected breeds. Association analysis illustrated the 7-nt variant was significantly associated with the litter size, duration of pregnancy, live lamb number, live lamb rate, stillbirth number, stillbirth rate of average and different parity ( P < 0.05) in AUW sheep. Moreover, 'ID' was the dominant genotype with excellent consistency in reproductive traits. It is instrumental to select individuals with ID genotype for improving the sheep reproduction traits. These findings suggest that the 7-nt variant within KDM3B gene can be used as a candidate marker of reproduction traits for sheep breeding improvement by marker-assisted selection.